RELASI ISLAM DAN HINDU DALAM PERSPEKTIF MASYARAKAT MULTIKULTUR DI BALI Studi Kasus Tiga Daerah: Denpasar; Karangasem, dan Buleleng - Suwindia, I Gede (Forum Ilmu Sosial, 2012)
This paper is motivated by the situations where Bali as part of the Unitary Republic of Indonesia that has a various diversity of ethnicity, race, religion, and citizenship. The background of various ethnic, tribe and religion in Indonesia are often tainted by the conflicts, contradictions, until riots. This makes this paper important to be appointed, where Bali gives a different color in managing the existing heterogeneity. When conflicts on behalf of ethnic, tribe and religion occurred in some areas, Bali remains in control, not affected by the riots. This article at least has the purpose to provide a review of the relation between the life that is built up during the time in Bali, especially between Muslims and Hindus in the perspective of multicultural society. The method used in this study is a qualitative method with descriptive analysis. Data sampling is done by using purposive sampling technique, using primary data in the form of informans and secondary data in the form of library data both at home and abroad as KITLV, as well as libraries at the University of Leiden. Islam and Hindu relationship in Bali is essentially strengthened in the Balinese culture that develops and continues sustainable until now. Genealogical role caused by inter-family marriages in the past, reinforce islam and hindu relationship. The role of kings in the past and to the present generation also contributed quite a bit of harmony of Islam and Hindu in Bali. Local government through Forum for Interreligious Harmony and Ministry of Religious Affairs gives greater media after the reform, so that there is better relations and places cultural piety as the foundation. The writer conclude that Islam and Hindu relationship in Bali is supported by the community local wisdom (Islam and Hindu), which upholds the sense of brotherhood, tolerance, respect, and recognition of the existing diversity. This reality is certainly very great significance in the life of the country of Indonesia.